A Proposal to Activate the Collective Waqf Platform Using the Blockchain Platform - Jordan as an Example - Sindyani, Qusai Mahmoud; Ababneh, Bayan Zuhier (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to present a proposal to activate the role of blockchain technology in the endowment sector in Jordan. In view of the prominent role that the endowment sector enjoys on the one hand, and on the other hand to benefit from and keep pace with developments and developments in the world of financial technology, and to project them onto the endowment sector, the study addressed the definition of endowment, smart endowment, and collective endowment. It also addressed the definition of blockchain technology, and an explanation of its advantages, and the advantages of this technology in The endowment sector, and how to activate it in the endowment sector, in addition to presenting practical models for applying blockchain technology in the endowment sector. The study also touched on presenting a proposed scenario for activating the role of blockchain technology in the endowment sector in Jordan. The study reached a number of results: Among the most prominent are: Financial technology can be used to serve the endowment sector. Using blockchain technology contributes to overcoming the problems that the endowment sector suffers from, enhances societal contribution to it, and expands the scope of its benefit. Implementing the idea of a collective endowment through blockchain technology; It contributes to alleviating pressure on the state budget and enhancing cooperation among members of Jordanian society. The study also recommends several recommendations, the most important of which are: 1. The study recommends the necessity of developing a special law and approving it by the Jordanian government. To benefit from the advantages of blockchain technology in Jordan, especially since it has a good internet infrastructure, and to make the endowment sector responsible for it. 2. The study recommends the necessity of implementing this proposal. To keep pace with developments in the field of financial technology; And enhancing opportunities for cooperation with neighboring countries in promoting this proposal.